Altered Metabolism of Leukemic Cells: New Therapeutic Opportunity - Starkova, Julia; Hermanova, Ivana; Hlozkova, Katerina; Hararova, Alzbeta; Trka, Jan (International review of cell and molecular biology, 2018)
The cancer metabolic program alters bioenergetic processes to meet the higher demands of tumor cells for biomass production, nucleotide synthesis, and NADPH-balancing redox homeostasis. It is widely accepted that cancer cells mostly utilize glycolysis, as opposed to normal cells, in which oxidative phosphorylation is the most employed bioenergetic process. Still, studies examining cancer metabolism had been overlooked for many decades, and it was only recently discovered that metabolic alterations affect both the oncogenic potential and therapeutic response. Since most of the published works concern solid tumors, in this comprehensive review, we aim to summarize knowledge about the metabolism of leukemia cells. Leukemia is a malignant disease that ranks first and fifth in cancer-related deaths in children and adults, respectively. Current treatment has reached its limits due to toxicity, and there has been a need for new therapeutic approaches. One of the possible scenarios is improved use of established drugs and another is to introduce new druggable targets. Herein, we aim to describe the complexity of leukemia metabolism and highlight cellular processes that could be targeted therapeutically and enhance the effectiveness of current treatments.
Keywords: Animals; Humans; zvířata; lidé; leukemie; Leukemia